Caloric Restriction Prevents Lead-Induced Oxidative Stress and Inflammation in Rat Liver - Mustafa Mohammadi; Rana Ghaznavi; Rana Keyhanmanesh; Hamid Reza Sadeghipour; Roya Naderi; Hossein Mohammadi (The Scientific World Journal)
The aim of the present study is to investigate the effects of caloric restriction on liver of lead-administered rat. Male Sprague-Dawley rats were randomly divided into two groups: Ad libitum fed group (AL, free access to normal rat chow) and caloric restriction group (CR, fed 65% of AL animals’ food intake). After 6 weeks, half of the animals of each group were injected lead acetate and the other half were injected saline. Liver tissue samples were collected at the end of the experiments. Glutathione peroxidase (GPx), superoxide dismutase (SOD), malondialdehyde (MDA), and tumor necrosis factor (TNF-α) were measured in the tissue extracts. Histological studies were also performed. Our results showed that lead administrations (not saline injections) reduced liver SOD and GPx and increased MDA and TNF-α in AL animals, but in the CR animals lead injections did not significantly change the measured parameters. The histological studies supported the biochemical findings. We concluded that 65% CR may prevent lead-induced oxidative stress and inflammation in rat liver.